A, The Role Of Notaries In Facilitating The Creation Of Partij Deeds For Individual Financing In Accordance With Fairness And Reasonableness: The Role Of Notaries In Facilitating The Creation Of Partij Deeds For Individual Financing In Accordance With Fairness And Reasonableness - Febrina Rizka Lilya Wati David (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to explore the role of notaries in ensuring legal certainty and promoting fairness and transparency in consumer financing. Using a qualitative approach and analyzing several consumer financing cases, the study finds that notaries play a critical role in ensuring the validity and legal protection of the agreements made. The main challenge lies in balancing the interests of creditors and debtors while ensuring that all relevant information about the agreements is disclosed transparently. Regulations such as Law No. 30 of 2004 on the Notary Position and Law No. 2 of 2014 on Amendments to Law No. 30 of 2004 on the Notary Position provide the legal framework for notaries' authority and responsibilities in consumer financing, although there is still a gap in regulations specifically addressing the notary's role in such transactions. This study recommends updating regulations and enhancing notary professionalism to better address these challenges. While the role of notaries is crucial, significant challenges in maintaining fairness and transparency still need to be addressed for consumer financing to be carried out equitably and transparently. Keywords: Notary; Legal Security; Consumer Financing